The acute neuropsychological effects of heading in soccer: a pilot study - Putukian, M.; Echemendia, R. J.; Mackin, S. (Clinical Journal of Sport Medicine, 2000)
OBJECTIVE: The main objective of this study was to prospectively examine the acute effects of heading in soccer on cognitive function. DESIGN: This was a prospective cross-over study using a brief neuropsychological battery to assess cognitive function. The tests were performed before and after two separate practice sessions, with athletes serving as their own controls. SETTING: Male and female Division I college athletes. PARTICIPANTS: Members of the men's and women's varsity collegiate Penn State University soccer teams. Forty-four males and 56 females entered and finished the study. All athletes had a normal physical examination. INTERVENTIONS: Before and after both practice sessions, all athletes had a brief battery of neuropsychological tests and a symptom checklist. MAIN OUTCOME MEASURES: Neuropsychological tests symptom checklist compared at baseline with those after the practice sessions. RESULTS: There were no significant differences in pretest scores between groups and no difference on posttest scores between heading and nonheading groups. A significant difference was detected using MANOVA (p = < 0.001) between pre- and posttest scores for measures of attention and concentration, indicating a practice effect. A gender-specific effect in one test measuring attention and concentration was found. There was no difference in symptoms before and after heading as compared with exertional controls. CONCLUSIONS: In this study, soccer players heading the ball does not appear to lead to acute changes in cognitive function as assessed by a brief neuropsychological battery. There are practice effects that occur with repetitive neuropsychological testing and gender differences with certain tests.